2018
DOI: 10.2141/jpsa.0170059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olive Leaf and Marigold Extracts on the Utilization of Nutrients and on Bone Mineralization using Two Different Oil Sources in Broilers

Abstract: The aim of this study was to investigate the effects of olive leaf and marigold extracts on the apparent total tract digestibility (ATTD) of the principal nutrients and energy, as well as on mineral utilization (Ca, P, Mg, Mn, Fe, Cu and Zn) in relation to bone characteristics in broilers fed walnut-or linseed oil-supplemented diets. Thirty-six 12-dayold commercial broilers Ross 308 were reared in metabolic cages, assigned to one of the six dietary treatments (3×2 factorial design): three supplements (not supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 77 publications
6
24
2
Order By: Relevance
“…In the present study the final live weight of broilers did not differ among the experimental groups, in agreement with results reported in similar studies (Herrero-Encinas et al, 2020;Leskovec et al, 2018;Varmaghany et al, 2013). On the other hand, Branciari et al (2017) observed significantly higher live weights in broilers fed with diets supplemented with olive cake.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study the final live weight of broilers did not differ among the experimental groups, in agreement with results reported in similar studies (Herrero-Encinas et al, 2020;Leskovec et al, 2018;Varmaghany et al, 2013). On the other hand, Branciari et al (2017) observed significantly higher live weights in broilers fed with diets supplemented with olive cake.…”
Section: Resultssupporting
confidence: 93%
“…The results of the present study agree with those of Leskovec et al (2018), who reported that dietary supplementation with olive leaf extract (1%) did not affect the physical properties (weight, length, maximum force and maximum bending) and crude ash content of the tibia of broilers. On the other hand, other studies have observed that polyphenols have an inhibitory effect on the secretion of digestive enzymes (α-amylase, protease and lipase), which may reduce the digestibility of nutrients (Surai, 2014).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings together suggest that the beneficial impacts of the olive leaf extract could be due to its well-demonstrated antioxidant, anti-inflammatory and antimicrobial activity. Contrary to these findings, other studies did not observe a significant impact of olive pomace extract on productive performances (King et al, 2014;Leskovec et al, 2017).…”
Section: Effec T Of P Olyphenol S On P Oultry Performan Cecontrasting
confidence: 75%
“…The results of this study showed that supplementation of different levels of OE or with M did not alter chicken performance during the different phases of the experiment. This is in agreement with Leskovec et al [44] in broiler chickens fed diets supplemented with an olive leaf extract. Furthermore, King et al [45] reported no significant differences in broiler performance after supplementing an olive pomace extract in water.…”
Section: Effect Of Olive Pomace Extractsupporting
confidence: 93%